SeCom: On Memory Construction and Retrieval for Personalized Conversational Agents - Pan, Zhuoshi; Wu, Qianhui; Jiang, Huiqiang; Luo, Xufang; Cheng, Hao; Li, Dongsheng; Yang, Yuqing; Lin, Chin-Yew; Zhao, H. Vicky; Qiu, Lili; Gao, Jianfeng (ICLR 2025, 2025)
To deliver coherent and personalized experiences in long-term conversations, existing approaches typically perform retrieval augmented response generation by constructing memory banks from conversation history at either the turn-level, session-level, or through summarization. In this paper, we present two key findings: (1) The granularity of memory unit matters: Turn-level, session-level, and summarization-based methods each exhibit limitations in both memory retrieval accuracy and the semantic quality of the retrieved content. (2) Prompt compression methods, such as LLMLingua-2, can effectively serve as a denoising mechanism, enhancing memory retrieval accuracy across different granularities. Building on these insights, we propose SeCom, a method that constructs the memory bank at segment level by introducing a conversation Segmentation model that partitions long-term conversations into topically coherent segments, while applying Compression based denoising on memory units to enhance memory retrieval. Experimental results show that SeCom exhibits a significant performance advantage over baselines on long-term conversation benchmarks LOCOMO and Long-MT-Bench+. Additionally, the proposed conversation segmentation method demonstrates superior performance on dialogue segmentation datasets such as DialSeg711, TIAGE, and SuperDialSeg.